A protein-centric approach for the identification of folate enzymes from the malarial parasite, Plasmodium falciparum, using OFFGEL™ solution-based isoelectric focussing and mass spectrometry - O'Cualain, Ronan DM (BioMed Central, 2010)
BACKGROUND: Plasmodium species are difficult to study using proteomic technology because they contain large amounts of haemoglobin-derived products (HDP), generated by parasite breakdown of host haemoglobin. HDP are known to interfere with isoelectric focussing, a cornerstone of fractionation strategies for the identification of proteins by mass spectrometry. In addition to the challenge presented by this material, as in most proteomes, there exists in this parasite a considerable dynamic range between proteins of high and low abundance. The enzymes of the folate pathway, a proven and widely used drug target, are included in the latter class. METHODS: This report describes a work-flow utilizing a parasite-specific extraction protocol that minimizes release of HDP into the lysate, followed by in-solution based OFFGEL™ electrophoresis at the protein level, trypsin digestion and mass spectrometric analysis. RESULTS: It is demonstrated that, by removing HDP from parasite lysates, OFFGEL™-mediated protein separation is able to deliver reduced complexity protein fractions. Importantly, proteins with similar and predictable physical properties are sharply focussed within such fractions. CONCLUSIONS: By following this novel workflow, data have been obtained which allow the unequivocal experimental identification by mass spectrometry of four of the six proteins involved in folate biosynthesis and recycling.